(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
The history of the creation of sur sheep in our country, the ways of their use in selection methods in the establishment of factory types, the processes of application of the methods used in livestock farms, and the results of their introduction in production are shown.